Quadriceps mechano‐ and electromyographic time‐frequency responses during muscular contractions to volitional exhaustion. Issue 3 (29th December 2015) - Croce, Ronald; Craft, Amber; Miller, John; Chamberlin, Kent; Filipovic, David
ABSTRACT: Introduction: Surface electromyography (SEMG) and mechanomyography (SMMG) responses of the quadriceps during muscular contractions to exhaustion were computed and analyzed by analysis of variance and polynomial regression analyses. Methods: Participants performed maximum flexion–extension movements at 180°/s until volitional exhaustion, rested for 2 minutes, and then completed a second bout of movements until exhaustion. Torque and SEMG/SMMG median frequencies and amplitudes were examined at 9 points across repetitions completed. Results: (1) Torque decreased precipitously; (2) SEMG amplitude displayed an initial increase, then a steady decrease, and SMMG amplitude showed a continuous decrease; and (3) SEMG and SMMG median frequencies displayed a continual decrease over repetitions completed. Fractional polynomial and quadratic models explained the fatigue process with the highest precision. Conclusions: Changes in electrical and mechanical properties of the quadriceps during fatigue reflect alterations in neuromuscular activation strategies and/or muscle wisdom. SEMG frequency modeled muscle fatigue more effectively than amplitude, whereas SMMG frequency and amplitude were equally effective. Muscle Nerve 53: 452–463, 2016